2003
DOI: 10.1093/toxsci/kfg073
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Studying Ochratoxin A (OTA)-Induced Nephrotoxicity: Expression Profiling in Vivo and in Vitro Employing cDNA Microarrays

Abstract: Ochratoxin A (OTA) is a mycotoxin often found in cereals as a contaminant, and it is known to cause severe nephrotoxicity in animals and humans. There have been several investigations studying the mode of action of this toxicant, suggesting inhibition of protein synthesis, formation of DNA adducts, and provocation of DNA single-strand breaks as a result of oxidative stress, but little is known about the transcriptional alterations underlying OTA-derived nephrotoxicity so far. We carried out DNA microarray anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
58
2
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(73 citation statements)
references
References 51 publications
11
58
2
1
Order By: Relevance
“…Similar stress-response molecular mechanisms have been reported to occur during tumor progression and in other models of cell toxicity in vitro (Salnikow et al 2002;Bando et al 2003;Luhe et al 2003;Fei et al 2004;Erler et al 2006;Hatzivassiliou et al 2005;Kanzawa et al 2005;Burton et al 2006). These findings suggest the possible involvement of hypoxia-related transcriptional activation in general cell survival strategies.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar stress-response molecular mechanisms have been reported to occur during tumor progression and in other models of cell toxicity in vitro (Salnikow et al 2002;Bando et al 2003;Luhe et al 2003;Fei et al 2004;Erler et al 2006;Hatzivassiliou et al 2005;Kanzawa et al 2005;Burton et al 2006). These findings suggest the possible involvement of hypoxia-related transcriptional activation in general cell survival strategies.…”
Section: Discussionsupporting
confidence: 67%
“…In our experimental model, a large number of up-regulated genes belonging to different functional pathways have previously been reported to be induced by the action of various noxious agents, which are able to produce stress insults resembling those occurring in hypoxic conditions (Goda et al 2003;Luhe et al 2003;Kanzawa et al 2005). In effect, a common denominator can be identified among the modulated genes (Table 1): many of them (23 out of 57) either are target genes of the hypoxia-inducible factor-1 (Hif-1), a heterodimeric (a/b) transcription factor playing a pivotal role in hypoxia, or share expression modulation under hypoxic conditions (Semenza et al 1994;Greijer et al 2005;LopezLazaro 2006;Papandreou et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…OTA-induced oxidative stress and ensuing DNA damage in combination with enhanced cell proliferation could increase the likelihood of neoplastic transformation (29). The presence of oxidative DNA damage, as also suggested by earlier findings (30)(31)(32), is supported by the up-regulation of the p53 pathway genes SUPT16H in both strains, MDM2 and CHEK2 in Eker rats, and RBBP6 in wild-type rats as well as by the time-dependent down-regulation of HSP 40-3, CN1, MSRA, and MGST1, responsible for the protection of cells against oxidative stress. Indeed, recent findings showed that overexpression of glia maturation growth factor h (GMFB) resulted in reduced antioxidant enzyme activities, subsequent accumulation of H 2 O 2 , and finally enhanced oxidative injury of renal proximal tubular cells (33).…”
Section: Discussionsupporting
confidence: 65%
“…In addition, Obrecht-Pflumio and Dirheimer [39] reported that ochratoxin is metabolized to genotoxic metabolites which interact with DNA may cause genetic damage in both target tissue independent of direct covalent binding to DNA. According to Luhe et al [40], the decrease cell proliferation could be due to OA toxicity, which alters trancripitional level of several genes known to be involved in DNA damage.…”
Section: Discussionmentioning
confidence: 99%